The reality of Primary School Teachers' Practice of Social Sciences to The Contemporary Professional Criteria - Qasim Jaleel Zayir Al-Ghurabi; Ramla Jabbar Khadhm Al-Saedi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
The study examines the extent to which primary school teachers in Maysan Province adhere to contemporary professional criteria in teaching social sciences, as perceived by school headmasters. Using a descriptive research approach, the study targeted 764 primary school principals during the (2024/2025) academic year, with a randomly selected sample of 150 participants (20% of the total population). A validated questionnaire comprising 65 items grouped into three areas—knowledge, skills, and values/attitudes—was used to assess teachers' practices. Data analysis employed several statistical tools, including percentages, chi-square, Cronbach's alpha, and others. Results revealed that the overall adherence to professional criteria was at a "good" level, with a weighted average of 163.063 (65.12%). Among the three areas, knowledge ranked highest (69.94%, very good), highlighting teachers' strong subject mastery and ability to effectively convey knowledge. Values and attitudes ranked second (63.78%, good), reflecting teachers’ commitment to ethical and professional standards. Skills ranked third (61.64%, good), indicating effective classroom management and use of modern teaching methods but showing room for improvement compared to the other areas. Based on these findings, the researcher recommended: designing training programs for social sciences teachers based on international standards, creating rewards and incentives for teachers meeting professional criteria, training headmasters in evaluation techniques aligned with contemporary standards, and updating social sciences curricula in Iraq to reflect global professional criteria. Further research on professional criteria in teaching at intermediate and preparatory levels was also suggested.